Selection of Ficus spp. species for rehabilitation of degraded land in Kuningan District, West Java, Indonesia - YAYAN HENDRAYANA; ILHAM ADHYA; DEDE KOSASIH; IMAM WIDHIONO; FAWAZ FAUZI ALFAHRI; INDRI SIGI APRIANTIKA; SURYA VAINES (Society for Indonesian Biodiversity, 2025)
Abstract. Hendrayana Y, Adhya I, Kosasih D, Widhiono I, Alfahri FF, Apriantika IS, Vaines S. 2025. Selection of Ficus spp. species for rehabilitation of degraded land in Kuningan District, West Java, Indonesia. Biodiversitas 26: 3199-3208. Land degradation is an environmental problem caused by various factors, including unsustainable land use, deforestation, and harmful agricultural practices. An effective method to overcome this problem is through land rehabilitation by replanting trees in the degraded areas. Therefore, this study aimed to select Ficus tree species for the rehabilitation of critical lands in Kuningan District, West Java, Indonesia. Data was collected using a field survey by making observation plots to document the presence of Ficus tree species in three land use types in the district, namely sand excavation area (Cidahu, Ciawigebang, and Japara Sub-districts), community gardens (Ciniru, and Hantara Sub-districts), and secondary forests (Selajambe, Subang, Cilebak Sub-districts). Vegetation analysis was conducted to calculate the importance value index and species similarity index. The results showed that there were 16 Ficus tree species across the surveyed locations with six species were found simultaneously in all three land uses, including F. benjamina, F. fistulosa, F. septic, F. variegata, F. ampelas, F. virens var. glabella. Other species included F. annulata, F. callosa, F. elastica, F. fulva, F. gibbosa, F. hispida, F. microcarpa, F. racemosa, F. sinuata, and F. subulata. Thus, the six species are recommended for the rehabilitation of degraded lands in Kuningan District.